Elucidating preparation-structure relationships for the morphology evolution during the RAFT dispersion polymerization of N-acryloyl thiomorpholine. Issue 11 (26th February 2021) - Sobotta, Fabian H.; Kuchenbrod, Maren T.; Grune, Christian; Fischer, Dagmar; Hoeppener, Stephanie; Brendel, Johannes C.
Abstract : Depending on the conditions, nearly monodisperse spherical micelles or complex morphologies are formed during a polymerization induced self-assembly (PISA) process based on the water-soluble monomer N -acryloylthiomorpholine. Abstract : Polymerization-induced self-assembly (PISA) is an emerging methodology for the in situ preparation of complex polymeric nanostructures in aqueous solution. However, the scope of monomers allowing morphology transitions remains limited, which is related to the low solubility of many monomers in water. Morphology transitions have therefore been restricted to more hydrophilic monomers necessitating rather long hydrophobic blocks to induce aggregation. Even longer ones are required to induce the changes of the morphology deviating from a spherical shape – a fact that limits the accessible hydrophobic domain sizes or morphologies. Here, we demonstrate that N -acryloyl thiomorpholine (NAT) represents a unique monomer which is fully miscible with water, but results in hydrophobic polymers at degrees of polymerization (DP) below 10, while morphology transitions can occur at DPs of 25 and even less. Synthesizing over 70 block copolymers in total we identified key parameters, such as hydrophilic block length, temperature, ratio of co-solvent, and concentration, influencing the self-assembly process. While the high glass transition temperature ( T g ) of PNAT may cause frozen and kinetically trapped micellar cores, suitable synthesis conditions enable access to all common morphologies including spheres, worms, and vesicles as well as intermediate phases. Applying this technique, various nanostructures are reproducibly formed in situ in aqueous dispersions rendering the presented PISA system a highly versatile, new route to functional block copolymer nanostructures for various applications.